2019
DOI: 10.5935/0103-507x.20190033
|View full text |Cite
|
Sign up to set email alerts
|

Availability of resources to treat sepsis in Brazil: a random sample of Brazilian institutions

Abstract: Objective To characterize resource availability from a nationally representative random sample of intensive care units in Brazil. Methods A structured online survey of participating units in the Sepsis PREvalence Assessment Database (SPREAD) study, a nationwide 1-day point prevalence survey to assess the burden of sepsis in Brazil, was sent to the medical director of each unit. Results A representative sample of 277 of the 317 invited units r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
1
10
0
3
Order By: Relevance
“…Since severe leptospirosis is a cause of sepsis (i.e. infection with organ dysfunction), lower availability of treatment resources are detrimental and unfortunately common in LMICs [10,11]. The present study from Miailhe et al reinforce that leptospirosis, albeit uncommon in some parts of the world, can have good outcomes if properly treated, but much worse outcomes in other areas with treatment resource limitations.…”
supporting
confidence: 57%
“…Since severe leptospirosis is a cause of sepsis (i.e. infection with organ dysfunction), lower availability of treatment resources are detrimental and unfortunately common in LMICs [10,11]. The present study from Miailhe et al reinforce that leptospirosis, albeit uncommon in some parts of the world, can have good outcomes if properly treated, but much worse outcomes in other areas with treatment resource limitations.…”
supporting
confidence: 57%
“…Sepsis is extremely dangerous, and the mortality rate is high. Worldwide, according to the World Health Organisation (WHO), there are millions of deaths from sepsis each year [12]. Li et al [13] showed that fever in patients with sepsis is a secondary reaction resulting from the release of endogenous pyrogens that include IL-1b and IL-6 from the activation of macrophages in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, lactate alone is neither sensitive nor specific enough to rule-in or rule-out the diagnosis on its own. Lactate testing may not be readily available in many resource-limited settings [54][55][56][57][58][59][60][61]. Therefore, we issued a weak recommendation favouring the use of serum lactate as an adjunctive test to modify the pretest probability of sepsis in patients with suspected but not confirmed sepsis.…”
Section: Rationalementioning
confidence: 99%